2023
DOI: 10.3233/mgc-220127
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new dihydrophenanthrene derivatives as promising anti-SARS-CoV-2 drugs through in silico investigations

Abstract: To research, evaluate, and invent novel compounds that inhibit SARS-CoV-2 activity, a series of reported 39 substituted 9, 10-dihydrophenanthrene derivatives were subjected to a quantitative structure-activity relationship (QSAR) study. Gaussian 09 and ChemOffice programs were used to calculate the molecular descriptors employed to determine their impact on the studied activity. Then we reduced the number of descriptors by eliminating the redundant information using principal component analysis (PCA). The crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The designed compounds with a high value of pIC 50 against alpha-glucosidase activity were subjected to an ADMET analysis for the purpose of gaining insight into the pharmacological properties which includes several properties such as the absorption, distribution, metabolism, excretion, and toxicity [ 49 , 50 ]. The pkCSM website is widely used for predicting these properties and evaluating the behavior of compounds in the human body.…”
Section: Methodsmentioning
confidence: 99%
“…The designed compounds with a high value of pIC 50 against alpha-glucosidase activity were subjected to an ADMET analysis for the purpose of gaining insight into the pharmacological properties which includes several properties such as the absorption, distribution, metabolism, excretion, and toxicity [ 49 , 50 ]. The pkCSM website is widely used for predicting these properties and evaluating the behavior of compounds in the human body.…”
Section: Methodsmentioning
confidence: 99%
“…According to the Lipinski, Veber, Ghose, and Egan rules as mentioned in Table 2, we evaluate the oral availability of remaining compounds, and the results are listed in Table S2 and revealed that only 50 compounds successfully exceeded the mentioned filters with no violation in the following properties: molecular weight of less than 500 Da, hydrogen bond donor of fewer than 5 bonds, hydrogen bond acceptors, and rotatable bonds of less than 10 bonds, in addition to the molecular refractivity fewer than 130 Å, and total polar surface area of less than 140 Å. [49] The ADMET properties of the remaining compounds were also assessed using pKCSM and Swiss-ADME online tool and listed in Table S2, Table S3 and Table S4.…”
Section: Oral Availability Of Analyzed Compoundsmentioning
confidence: 99%
“…The molecular docking simulations were performed using the Autodock4 program (Trott and Olson 2009), which employs an empirical scoring function to evaluate the binding a nity between the receptor and ligands. The docking simulations provide insights into the potential binding modes and interactions between the ligands and the receptor (Abchir et al 2022;Yamari et al 2023). In summary, the material and methods of molecular docking involved the retrieval and optimization of the receptor structure, preparation of the receptor and ligands in the appropriate format, de nition of the binding site using a grid box, and the actual docking simulations performed with the Autodock4 program.…”
Section: Molecular Docking Studymentioning
confidence: 99%